Literature Review: Analysis of The Use of Realistic Mathematics Education (RME) On The Problem-Solving Ability of Students in Elementary Schools - Ferlia Putri Rahmania; Turmudi (International Conference on Elementary Education, 2023)
Innovation in learning is one of the efforts that can be made by educators to achieve the expected learning outcomes. This study aims to analyze, describe and discuss the use of Realistic Mathematics Education (RME) on students' problem-solving abilities in elementary schools. The method used in this research is SLR (Systematic Literature Review). This research uses sheet analysis of articles as a research instrument. The first step taken was to collect related articles published in the 2019-2021 period with sources from Google Scholar, sort the data, analyze the articles, summarize the discussion, and make conclusions. The articles used in this study were seven journal articles. The results of the study found that the use of RME in learning activities had a positive impact on the problem-solving abilities of elementary school students. This can happen because RME essentially means three things: (1) the real context in everyday life; (2) formal mathematical context in mathematics; or (3) an imaginary context that the mind can imagine.